Pengaruh Debt To Equity Ratio Dan Kepemilikan Manajerial Terhadap Nilai Perusahaan Dengan Ukuran Perusahaan Sebagai Variabel Moderasi Pada Perusahaan Sektor Consumer Non Cyclicals Yang Terdaftar Di Bursa Efek Indonesia Periode 2020-2024 - Awam Mukhatam Riziq; Elfiswandi .; Putri Intan Permata Sari (CV. ITTC INDONESIA, 2026)
Firm value is an important indicator in assessing a company's performance and success, as reflected in its stock price. In the non-cyclical consumer sector, firm value tends to fluctuate, influenced by various factors, including the debt-to-equity ratio and managerial ownership. Furthermore, firm size is also thought to strengthen or weaken this relationship. This study aims to analyze the effect of the debt-to-equity ratio and managerial ownership on firm value, with firm size as a moderating variable. This study uses a quantitative approach with an associative research type. The study population is non-cyclical consumer sector companies listed on the Indonesia Stock Exchange for the 2020–2024 period. The sampling technique used purposive sampling, resulting in 30 companies with a total of 150 observations after data processing and outlier handling. Data collection techniques used documentation from the official Indonesia Stock Exchange website and secondary data sources using panel data regression analysis methods. The results show that the debt-to-equity ratio has a significant effect on firm value, while managerial ownership has no significant effect on firm value. Testing of moderating variables shows that firm size can strengthen the effect of the debt-to-equity ratio on firm value, but weakens the effect of managerial ownership on firm value. The conclusion of this study indicates that the debt-to-equity ratio is a significant factor in increasing company value, while managerial ownership has not made a significant contribution. Company size acts as a moderating variable, and therefore should be taken into consideration by investors and management when making decisions.